The Impact of Immigrants on Public Finances: A Forecast Analysis for Denmark - Marianne Frank Hansen; Marie Louise Schultz-Nielsen; Torben Tranæs (Institute for the Study of Labor (IZA), 2015)
All over Europe, ageing populations threaten nations' financial sustainability. In this paper we examine the potential of immigration to strengthen financial sustainability. We look at a particularly challenging case, namely that of Denmark, which has extensive tax-financed welfare programmes that provide a high social safety net. The analysis is based on a forecast for the entire Danish economy made using a dynamic computable general equilibrium model with overlapping generations. Net contributions to the public purse are presented both as cross-sectional figures for a long time horizon and as average individual life-cycle contributions. The main conclusion is that immigrants from richer countries have a positive fiscal impact, while immigrants from poorer countries have a large negative one. The negative effect is caused by both a weak labour market performance and early retirement in combination with the universal Danish welfare schemes.
Keywords: F22; E62; J61; 330; immigration; sustainable fiscal policy; welfare benefits